"It can hit anybody": protest actors' frames of repression during times of states of emergency in France = "Es kann jede:n treffen" : Frames von Repression durch Protestakteur:innen in Zeiten von Ausnahmezuständen in Frankreich - Fritsch, Katharina (Kriminologisches Journal, 2025)
In recent years, French politics have been shaped by states of emergency, more specifically an anti-terrorist and sanitary state of emergency. At the same time, France’s public sphere has been marked by large protest movements, which have often faced state repression. Based on problem-centred interviews with protest actors belonging to environmental movements, antiracist movements and social justice movements (yellow vests, anti-gentrification) in France, with a focus on Marseille, I discuss how social movement actors frame repression, and in particular how they problematise repression. Their frames of soft and hard repression show how contemporary French protest policing has been shaped by politics of exception, which include formal states of emergency as well as petty states of exception. Focusing on anti-terror and police violence frames, I argue that the intensification and expansion of protest repression through politics of exception is accompanied by experiences of intensified racialised othering, as well as an extensive framing of protest as an Other to the Republic. Politics of exception are thus revealing of de-democratisation processes and postcolonial contexts of exceptional policing.